The jumping spider genus Nycerella Galiano, 1982 in Brazil, with description of the female of Nycerella melanopygia Galiano, 1982 (Araneae: Salticidae: Freyina) - Ruiz, Gustavo R.S.; Paz, Alexia Vaughan; Bustamante, Abel Antonio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Three species of Nycerella Galiano, 1982 have been recorded from Brazil: N. aprica (Peckham & Peckham, 1896), N. melanopygia Galiano, 1982 and N. volucripes Galiano, 1982. The female of N. melanopygia, however, remains undescribed. Herein, we describe the female of N. melanopygia for the first time, and give additional geographical records for the three species mentioned above, extending their distributions all the way to northeastern states of Brazil.